The Role of Islamic Boarding School Darul Mukhlisin Indonesian Muslim University in Improving Community Welfare in Padanglampe, Pangkep Regency - Andi Hasriani; St Samsudduha (Lembaga Sembilan Tiga Community, 2020)
This study discusses community-based empowerment of the Darul Mukhlisin Pangkep Student Boarding School in improving the welfare of the surrounding community. The purpose of this study was to determine the efforts made by pesantren and community involvement in improving their welfare. This study uses qualitative data collection methods by earlier determining the research location, research focus, and research subjects. The data collection method starts with observation, interviews, literature, and documentation. Followed by data analysis in the hope of facilitating the research process. As for the findings in this study, Darul Mukhlisin's student boarding school has a role in improving the community's economy in the village of Padanglampe. Since the presence of pesantren, people's lives have slowly undergone changes in the economic field. This is due to the pesantren involving the community to be able to work in pesantren with various kinds of jobs available. In addition, the pesantren gives permission to the surrounding community to open their own jobs in the vicinity of the pesantren such as opening shops and stalls that provide the needs of the community and also the needs of students, so that people increasingly benefit from the existence of the Darul Mukhlisin Islamic Boarding School.